Collaboration meeting between Universitas Muslim Nusantara Al Washliyah, Indonesia (UMNAW) and Universiti Teknologi Mara Kelantan Branch (UiTMCK) - UiTM Cawangan Kelantan, Department of International Affairs (2022)
MACHANG, 2 November - The Department of International Affairs (DIA) UiTMCK has organised an international collaboration meeting with Universitas Muslim Nusantara Al Washliyah, Indonesia (UMNAW) on 17 October 2022 (Monday). The meeting was held at HRDA, UiTMCK. The meeting was chaired by Prof. Dr Haji Abdol Samad Nawi, Rector of UiTMCK. The meeting was also participated by thetop management of UiTMCK, Assoc. Prof. Ts. Dr Mohd Nasir Ismail, Deputy Rector of Academic Affairs, Encik Farouk Meer Zhar Amir Razli, Deputy Rector of Student Affairs, Dr Syerina Azlin Md Nasir, Deputy Rector of Research, Industrial Linkages& Alumni, UiTMCK as well as the Heads of Faculties of UiTMCK. UMNAW was represented by Dr KRT Hardi Mulyono K Surbakti, Rector of UMNAW, Dr Firmansyah M.Si., Vice Rector of Academic Field, Dr Ridwanto, M.Si, Vice-Rector for Finance and HR, Deans and Heads of Department.